2020
DOI: 10.3390/su12187485
|View full text |Cite
|
Sign up to set email alerts
|

Does Chinese FDI, Climate Change, and CO2 Emissions Stimulate Agricultural Productivity? An Empirical Evidence from Pakistan

Abstract: Pakistan’s agricultural sector growth is dwindling from the last several years due to insufficient foreign direct investment (FDI) and a drastic climate change-induced raise in temperature, which are severely affecting agricultural production. The FDI has paramount importance for the economy of developing countries as well as the improvement of agricultural production. Based on the time series data from 1984 to 2017, this paper aims to highlight the present situation of the agriculture sector of Pakistan and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…It implies that 1% increase in the level of precipitation will lead to improve rice production by 0.20% and 0.19% in the long and short run. The results agree with the research of (Ahmad et al 2020;Ali et al 2017;Sossou et al 2019;Zaied and Cheikh 2015). Khan et al (2019) explored that the maximum level of temperature has a negative influence on maize production while rainfall positively improves maize production in Pakistan.…”
Section: Results Of Vecm-based Ganger Causality Tests For Model (I)supporting
confidence: 89%
See 3 more Smart Citations
“…It implies that 1% increase in the level of precipitation will lead to improve rice production by 0.20% and 0.19% in the long and short run. The results agree with the research of (Ahmad et al 2020;Ali et al 2017;Sossou et al 2019;Zaied and Cheikh 2015). Khan et al (2019) explored that the maximum level of temperature has a negative influence on maize production while rainfall positively improves maize production in Pakistan.…”
Section: Results Of Vecm-based Ganger Causality Tests For Model (I)supporting
confidence: 89%
“…It implies that 1% increase in precipitation level will increase wheat production by 0.06% and 0.08%. The findings of precipitation are strongly substantiated by Ahmad et al (2020) and Zaied and Cheikh (2015), who found that precipitation positively improved crop production.…”
Section: Long-and Short-run Estimates For Model (I)mentioning
confidence: 76%
See 2 more Smart Citations
“…This is particularly true for the agricultural sector since the increase in average annual temperature and other climatic changes are deteriorating the productivity growth of this sector and aggravating global food insecurities (Abbas, 2020;IPCC, 2014;Kotir, 2011). Many species of agricultural crops are highly sensitive to climatic changes associated with increasing temperature, changing pattern and intensity of rainfall, concentration of carbon dioxide (CO2), rising sea level, and intensity of natural disasters (Ahmad et al, 2020;Boonwichai et al, 2019;Mendelsohn, 2014).…”
Section: Introductionmentioning
confidence: 99%